Pengembangan E-Modul Interaktif (Edultif) untuk Meningkatkan Pemahaman Nilai-Nilai Pancasila Sila Kelima Pada Siswa Kelas IV Sekolah Dasar - Laila, Laila Syamlatul Zanah; Titin Sunaryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
E-modules are electronic-based teaching materials commonly used in learning, but accessed through technology. This research aims to develop an interactive e-module (Edultif) to improve the understanding of the fifth principle of Pancasila among fourth grade students at SD Negeri Sukamanah 02. The research method employed was Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects were 28 fourth grade students. Data were collected through expert validation, observation, teacher and student response questionnaires, as well as pretest and posttest. Expert validation results indicated that the interactive e-module was feasible to use (average score > 96%). The effectiveness test showed an increase in students’ understanding, indicated by an average pretest score of 73 (Fair category) rising to 87 in the posttest (Good category) with an N-gain of 0.52 (Medium category). The teacher and student response questionnaires indicated that the interactive e-module is practical for use in PPKN learning. It can be concluded that the interactive e-module is effective, valid, and practical for improving students’ understanding of the fifth principle of Pancasila in elementary schools.